The role of institutions in finance curse: evidence from international data - Law, Siong Hook; Kutan, Ali M.; Niaz Ahmad, Mohd Naseem (Elsevier, 2018)
This paper investigates the effect of banking sector development on economic growth in a panel of 87 countries, paying particular attention to the role of institutions in reducing the finance curse phenomenon. The dynamic generalized method-of-moments (GMM) results indicate that institutions play an important role in mediating the positive relationship between banking sector development and growth. This suggests that the marginal impact of financial development on growth depends on institutional quality. Using the four-way partition of institutions classified by Rodrik (2005), we also find that resilient market-regulating, market-stabilizing, and market-creating institutions act as mediators to the financial market in facilitating growth. The results are robust to using alternative institutions indicators, estimation strategies, and stopping the sample before the 2007-2008 global financial crisis.